Psychiatric Symptoms and Parental Stress in Children and Adolescents With Epilepsy - Operto, Francesca Felicia; Pastorino, Grazia Maria Giovanna; Pippa, Federica; Padovano, Chiara; Vivenzio, Valentina; Scuoppo, Chiara; Pistola, Ilaria; Coppola, Giangennaro (Frontiers in Neurology, 2021)
Introduction: The aim of our study was to identify the presence of emotional and behavioral symptoms in children and adolescents with epilepsy, to measure the stress levels in their parents and to determine if and how parental stress was linked to emotional/behavioral symptoms of their children. Methods: We conducted a cross-sectional observational study including 103 children and adolescents with different form of epilepsy and 93 sex/age-matched controls. Parental stress and emotional/behavioral symptoms was assessed through two standardized questionnaires: the Parenting Stress Index (PSI) and the Child Behaviour Checklist (CBCL) respectively. We also considered the following variables: age, sex, maternal education level, family history of psychiatric disorders, duration of epilepsy, seizure frequency, seizure type, number of antiseizure medications. Results: The statistical comparison showed that the epilepsy group obtained significantly higher scores than controls in almost all the CBCL and PSI scales (p<0.05). The correlation analysis revealed a significant relationship between the PSI Total Stress scale and the following CBCL scales: Total Problems, Internalizing Problems and Externalizing Problems (p<0.05). An earlier age of seizure onset was related to a greater presence of Externalizing Problems, Total Problems, and Total Stress (p<0.05). Conclusions: In the epilepsy group we found higher levels of parental stress and higher presence of emotional/behavioral symptoms compared to controls, mainly represented by internalizing problems (anxiety and depression symptoms). Therefore, it is important to precociously detect these symptoms and monitor them over time, in order to prevent psychiatric problems. In addition, parents of children with epilepsy should be offered psychological support to cope with parental stress and to improve the relationship with their children.